THE IMPACT OF NEW MEDIA ON CHILDREN 6-12 YEARS IN INDONESIA - Marwan, M Ravii; Nuke Farida (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aims to analyze how the impact of the media on children aged 6-12 years. The research method used by the researcher uses a qualitative-descriptive method which focuses on understanding the process and also understanding phenomena as well as describing the situation in the current era. As well as using Literature Studies which conduct studies related to theory. The analysis uses Computer Mediated Communication Theory where the use of computers is a technological development that facilitates communication between people without having to meet face to face in different places. The results of the research, researchers show that the influence of technology, especially gadgets for early childhood is very influential & has an impact on the development of children's mindsets, where the role of parents is needed to avoid the negative effects of using technology at an early age. From the research that has been made, it can be concluded that there are negative and positive impacts on children. The positive impact is in the form of being able to train creativity for children's brain intelligence, a means of sharing together, as well as a means of socialization media among others. There are negative impacts in the form of health problems in the child's body, apathy and indifference to the surrounding environment, easily emotional, and so on.